Evaluasi diri (self-assessment) sebagai strategi penilaian autentik dalam pembelajaran - Uswatun Khasanah; Madiun Alfiyatu Sa’diyah (Universitas PGRI Madiun, 2026)
Self-assessment is a form of authentic assessment that actively involves students in evaluating their own abilities, learning process, and outcomes based on certain criteria. This article examines the concept, purposes, benefits, principles, implementation steps, strengths and weaknesses, and examples of self-assessment application in learning through a literature review method. The results show that self-assessment provides significant benefits for both students and teachers, including increasing self-awareness, learning responsibility, reflective thinking, and self-regulated learning. However, its implementation also has limitations, such as the potential lack of objectivity in students' self-evaluation, so teacher guidance remains necessary to obtain more accurate results. Self-assessment can be implemented through various instruments such as reflection sheets, learning journals, checklists, rubrics, and portfolios, making it a relevant strategy for twenty-first century learning.